IUD insertion transcesarean TCU 200 long filament - Vargas B., Francisco (2015)
This work is new in our institution and our country. The IUD TCu 200 long filament, is used for the first time in this hospital and the patient being operated cesarean and needs a reasonable spacing of their next child is given, valuing the high reproductive risk, which means intergenesic period short and the possibility of uterine rupture increases in this period. Also, we consider that we have used the TCu 200 with long filament, which facilitates placement and location of this guide, leaving the cervix, due to its size (35 cm) and thus allows an easy location IUD by the cervix. This device was provided for study by the Mexican Academy of Medical Research in Demography.